Assessment of community pharmacists' communication and comfort levels when interacting with Deaf and hard of hearing patients - Elizabeth Y. Chong; Sabrina A. Jacob; Amutha Ramadas; Pei H. Goh; Uma D. Palanisamy (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: Deaf and hard of hearing patients who use sign language face considerable communication barriers while accessing pharmacy services. Low comfort-levels between community pharmacists and Deaf and hard of hearing patients result in poor interactions and increase patient safety risks. Objective: 1) To examine the way community pharmacists interact with Deaf and hard of hearing patients in Malaysia, and their level of comfort in such interactions. 2) To examine how comfort-levels vary by the preferred communication methods, resources and employer support. Methods: This cross-sectional study was conducted among registered community pharmacists practicing in Malaysia. Questionnaire items included comfort-levels of community pharmacists when interacting with Deaf and hard of hearing patients, used and preferred communication methods, necessary resources, and perceived employer's level of support. Based on the list of registered pharmacies, the questionnaire with a pre-paid return envelope was mailed out while pharmacies close to the university were approached in person. This questionnaire was distributed online using Google Form. Comparisons between comfort-levels and study parameters were analyzed using independent t-tests and ANOVA. Results: A total of 297 community pharmacists responded (response rate 29.2%). Higher comfort-levels were reported in those who had received between 1 to 5 prescriptions as compared to those who did not receive prescriptions from Deaf and hard of hearing patients (MD= -0.257, SD=0.104, p=0.042). More than 80% used written information and only 3.4% had used the services of a qualified sign language interpreter throughout their community pharmacist career. Significantly lower comfort-levels (p=0.0004) were reported in community pharmacists who perceived training in sign language as a necessity to interact with Deaf and hard of hearing patients (M=3.6, SD=0.9) versus those who were not interested in sign language training (M=3.8, SD=0.6). Conclusions: The results suggest that community pharmacists were neither extremely comfortable nor averse when interacting with Deaf and hard of hearing patients. The lack of significant findings in terms of comfort-levels may indicate other potential drivers for their choice of communication method when interacting with Deaf and hard of hearing patients.